DNA methylation at individual CpG-sites of EPB41L3, HTERT and FAM19A4 are useful for detection of cervical high-grade squamous intraepithelial lesions (HSIL) or worse: Analysis of individual CpG-sites outperforms averaging - Monica Molano; Dorothy A. Machalek; Samuel Phillips; Grace Tan; Suzanne M. Garland; David Hawkes; Prisha Balgovind; Reza Haqshenas; Steve G. Badman; John Bolnga; Josephine Gabuzzi; Zure Kombati; et al. (Tumour Virus Research, 2024)
Global methylation analysis of gene promoters is promising for detection of high-grade squamous intraepithelial lesions or worse (HSIL+) in high-risk human papillomavirus (hrHPV)-positive women. However, diagnostic performance of methylation data at individual CpG-sites is limited. We explored methylation for predicting HSIL+ in self- and clinician-collected samples from Papua New Guinea.Methylation of EPB41L3 (1–6 CpG-sites), hTERT (1–10 CpG-sites) and FAM19A4 (1–5 CpG-sites) was assessed through pyrosequencing from 44 HPV+ samples (4 cancers, 19 HSIL, 4 low-grade squamous intraepithelial lesions (LSIL), 17 normal). New primers were designed for FAM19A4 directed to the first exon region not explored previously.In clinician-collected samples, methylation at CpG-sites 4 and 5 of EPB41L3 were the best HSIL predictors (AUC >0.83) and CpG-site 4 for cancer (0.925). Combination of EPB41L3 sites 2/4 plus FAM19A4 site 1 were the best HSIL+ markers [100% sensitivity, 63.2% specificity].Methylation at CpG-site 5 of FAM19A4 was the best HSIL predictor (0.67) in self-collected samples, and CpG-sites 1 and 3 of FAM19A4 for cancer (0.77). Combined, FAM19A4 site 1 plus HPV 16/18 detection yielded sensitivity of 82.6% and specificity of 61.9%.In conclusion, methylation at individual CpG-sites of EPB41L3 and FAM19A4 outperformed global analysis and improved HSIL+ detection, warranting further investigation.